EDUKASI PEMERTAHANAN BAHASA BUGIS PADA RANAH KELUARGA DI DESA BONTOMACINNA KECAMATAN GANTARANG KABUPATEN BULUKUMBA - Zulkhaeriyah Zulkhaeriyah (JCS, 2021)
The maintenance of a local language is a symbol of the survival of the concept of traditional cultural values. The loss or extinction of local languages, including Buginese, will also disappear and extinct the concept of traditional cultural values because traditional culture can only be understood properly through the expression of the local language of the people. In other words, if local languages become extinct, the image and identity of the people will become unclear. By raising the case for the maintenance of the Buginese in Bulukumba Regency, this Community Service aims to (1) describe the patterns of Buginese maintenance in the family domain in Bulukumba Regency and (2) analyze the factors that support the preservation of the Buginese in Bulukumba Regency, South Sulawesi Province. The method used is an approach through educating the local people to keep using the Buginese in the family realm. The results of the activity show that the Bugis people still maintain their language in the realm of a good family. Factors that support the maintenance of the Buginese in Bontomacinna Village are loyalty, awareness of the norm, language pride, age, and occupation.